Frostbite : a [Vampire Academy novel] - Mead, Richelle (New York : Razorbill, 2008)
While on a school skiing trip, guardian-in-training Rose faces everything from misunderstandings between friends to fights among factions of Moroi as reports of horrific Strigoi attacks raise tensions, ultimately leading Rose and some of those closest to her into a battle that teaches her much about life, death, and love.
Keywords: Vampires -- Fiction; Skis and skiing -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Magic -- Fiction; Social classes -- Fiction